2011
DOI: 10.1186/1752-1947-5-399
|View full text |Cite
|
Sign up to set email alerts
|

Lipid rescue of massive verapamil overdose: a case report

Abstract: IntroductionMassive intentional verapamil overdose is a toxic ingestion which can cause multiorgan system failure and has no currently known antidote.Case PresentationThe patient is a 41-year-old Caucasian woman who ingested 19.2 g of sustained release verapamil in a suicide attempt. Our patient became hypotensive requiring three high-dose vasopressors to maintain arterial pressure. She also developed acute respiratory failure, bradycardic ventricular rhythm necessitating continuous transvenous pacing, and anu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 26 publications
0
30
1
Order By: Relevance
“…These findings are in contrast to several animal and human studies that have demonstrated hemodynamic benefit with ILE administration in various drug classes, including calcium channel blockers, 19,23,24 amiodarone, 48 betablockers, 15 and tricyclic antidepressants. 20,26,28 The observational nature of our study, compared to the randomized, controlled design of many of the animal and human studies, is the most likely explanation for the difference.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings are in contrast to several animal and human studies that have demonstrated hemodynamic benefit with ILE administration in various drug classes, including calcium channel blockers, 19,23,24 amiodarone, 48 betablockers, 15 and tricyclic antidepressants. 20,26,28 The observational nature of our study, compared to the randomized, controlled design of many of the animal and human studies, is the most likely explanation for the difference.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike previously published human case reports, we enrolled consecutive patients that received ILE therapy and our results included patients that survived or died after the administration of ILE. The majority of published case reports on the utility of ILE in this setting have positive outcomes, [22][23][24][25][26][27][28][29][30][31][32] although negative case reports on the effect of ILE in overdose patients have also been published. 54,55 Limitations Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al (11) concluded that intravenous lipid treatment was found to be effective in massive calcium channel blocker overdose, and its early start in the case of hemodynamic compromise was recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these cases involve verapamil or diltiazem. Nifedipine was cited in two publications in which both patients survived [7,24]. There are three published toxic cases of another dihydropyridine, amlodipine, where ILE was included in therapy; two survived [7,16].…”
Section: Discussionmentioning
confidence: 99%